Security Laws and Children in Prison: The Issue of Psychological Impact - Dawes, A. (PINS-Psychology in Society, 1987)
In order to situate the debate on this topic, I shall highlight what seem to me to be three central issues. There are the political: the reasons for state oppression of youth, the notion of childhood inherent in certain appeals on behalf of incarcerated children, and the manner in which provisions of the law regarding children are overridden by security legislation. “Children” as referred to in the paper, concerns persons under the age of 18 who are legally classified as not having attained adult status and for whom special provision exists within Common law, the Criminal Procedure Act 61 of 1977 and the Child Care Act 74 of 1983. The term youth will be used to refer to those between the ages of 18 and 23, being an age definition coined by Keniston (1970) to refer to students at tertiary institutions of education and young workers.